1997
DOI: 10.1037/0022-0663.89.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the motivational beliefs of Asian American and non-Asian students.

Abstract: This investigation explored differences in motivational beliefs of 154 Asian American and 372 non-Asian 9th graders. Students completed surveys indicating their academic beliefs and later responded to a novel task to assess their achievement behavior. The difference in type of beliefs between the two groups explained, in part, their achievement behavior. Asian American students' fear of the consequence of academic failure best explained their performance. However, this variable least explained the results for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 63 publications
11
141
1
5
Order By: Relevance
“…The respect for parental views has also been found to be a common feature of Asian students' attitudes (e.g. Eaton and Dembo, 1997), while the learners' general desire to succeed academically in their new school is confirmed by the fact that only 24% believe that English is more important than other subjects.…”
Section: The Importance Of Englishmentioning
confidence: 89%
“…The respect for parental views has also been found to be a common feature of Asian students' attitudes (e.g. Eaton and Dembo, 1997), while the learners' general desire to succeed academically in their new school is confirmed by the fact that only 24% believe that English is more important than other subjects.…”
Section: The Importance Of Englishmentioning
confidence: 89%
“…Evidence regarding the mediating role of academic self-efficacy among Asian American students is scarce, but a study by Eaton and Dembo (1997) found that, on average, Asian American ninth graders had lower academic self-efficacy beliefs but higher achievement behaviors compared to non-Asian American students, suggesting that academic selfefficacy may not be responsible for the high achievement of this group. Correlations indicated that fear of failure was significantly associated with academic achievement for the Asian American students, but that self-efficacy beliefs were not.…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 99%
“…Other fields of the social sciences, such as sociology, have conducted studies to examine achievement motivation among some minority populations (Rumberger & Larson, 1998;Anderson & Evans, 1976;Eaton & Dembo, 1997;Evans & Anderson, 1973). Unfortunately, the findings from this work are limited because those researchers have tended to use grade point average (Rumberger & Larson, 1998), test scores (Eaton & Dembo, 1997;Rumberger & Larson, 1998) or parental focus on achievement (Anderson & Evans, 1976) as proxies for motivation. The use of such measures runs the risk of confounding achievement motivation with its presumed outcomes.…”
mentioning
confidence: 99%